2001
DOI: 10.1016/s0378-1097(01)00375-5
|View full text |Cite
|
Sign up to set email alerts
|

K+ influx by Kup in Escherichia coli is accompanied by a decrease in H+ efflux

Abstract: Escherichia coli accumulates K by means of multiple uptake systems of which Kup is the major transport system at acidic pH. In cells grown under fermentative conditions at pH 5.5, K influx by a wild-type strain upon hyper-osmotic stress at pH 5.5 was accompanied by a marked decrease in H efflux, with a 1:1 ratio of K to H fluxes. This was observed with cells treated with N,NP-dicyclohexylcarbodiimide. Similar results with a mutant defective in Kdp and TrkA but with a functional Kup system but not in a mutant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The Kdp system is a high-affinity K ϩ transport system that is induced in low-K ϩ environments (K ϩ concentration, 5 mM or less) (15,17). The Kup system has an affinity for K ϩ similar to that of the Trk system and is believed to be the major K ϩ transport system under acidic conditions (44,48). Previous studies showed that Salmonella trkA (sapG), which encodes an essential NAD ϩ binding subunit of the Trk system, was necessary for resistance to antimicrobial peptides (37).…”
mentioning
confidence: 99%
“…The Kdp system is a high-affinity K ϩ transport system that is induced in low-K ϩ environments (K ϩ concentration, 5 mM or less) (15,17). The Kup system has an affinity for K ϩ similar to that of the Trk system and is believed to be the major K ϩ transport system under acidic conditions (44,48). Previous studies showed that Salmonella trkA (sapG), which encodes an essential NAD ϩ binding subunit of the Trk system, was necessary for resistance to antimicrobial peptides (37).…”
mentioning
confidence: 99%
“…Moreover, there is increasing evidence suggesting that many KT-HAK-KUP transporters are low-affinity transporters (Quintero and Blatt, 1997;Senn et al, 2001), which apparently overlap their K ϩ concentration range of activities with K ϩ channels. This apparent duplication of transporters with similar affinities for K ϩ could be explained if transporters of the Kup-HAK family mediated active K ϩ -H ϩ cotransport (Rodríguez-Navarro, 2000; Zakharyan and Trchounian, 2001), and the other transporters were uniporters allowing only electrochemical equilibrium. This hypothesis would give a good explanation for the extensive existence of Kup-HAK family of transporters in so many different organisms, but needs to be proved.…”
mentioning
confidence: 99%
“…Escherichia coli wild type strain K-12(k) was grown in peptone medium (0.2% peptone, 0.5% NaCl, and 0.2% K 2 HPO 4 , pH 7.5), under anaerobic conditions upon glucose (0.2%) fermentation at 37°C till stationary growth phase (18-20 h) [11,14,15,24,25]. Grown and concentrated cells were transferred into bi-distilled water or into assay buffer (150 mM Tris-phosphate buffer containing 0.4 mM MgSO 4 , 1 mM KCl, and 1 mM NaCl, pH 7.5).…”
Section: Bacteria and Preparation To Experimentsmentioning
confidence: 99%
“…The SigmaPlot software [28] were used for determination of the standard errors (\3%) and the Student's t test calculation with the validity criteria (P) (validity for the difference between the changed values for each average data and the nonirradiated control) [29]. The statistical analysis used was effectively applied elsewhere [10,24,30].…”
Section: Data Processingmentioning
confidence: 99%